Assessment of breeding nuclei contributions to the genetic diversity and population structure of the Cyprus Chios sheep - Andreas C. Dimitriou; Giannis Maimaris; Georgia Hadjipavlou (Scientific Reports, 2024)
Abstract Cyprus, facing climate change and desertification, has Europe’s second highest population growth. Halloumi cheese’s Protected Designation of Origin status boosted goat and sheep milk demand. Optimizing primary sector production is key to balancing food production and environmental sustainability. The present study aims to explore the genetic diversity and population structure of Cyprus Chios sheep, as well as the impact of existing breeding nuclei on the breed’s gene pool. Two breeding nuclei aiming to preserve genetic diversity and boost local milk production and four private farms were sampled. Genome-wide data using Illumina 50 K arrays were generated, analyzing over 1000 animals from six farms. At least three distinct genetic groups were identified, two of which are represented by the nuclei’s distinct genetic profiles and a third was found in private farms. Calculated metrics indicate a negative correlation of gene flow with geographic distance in case of the Eastern nucleus. Presented results support recent, though limited inbreeding (mean FROH=0.046), compared to other commercial breeds. Estimated effective population size reveals a stabilizing trend to a relatively high number (Ne ~ 200) which indicates relatively high diversity that allows further genetic improvement. Revealed genomic diversity highlights the necessity of such exploration before effectively implementing genomic evaluation programs.